Graph analysis of verbal fluency test discriminate between patients with Alzheimer's disease, mild cognitive impairment and normal elderly controls - Bertola, Laiss; Mota, Natália B.; Copelli, Mauro; Rivero, Thiago; Diniz, Breno Satler; Romano-Silva, Marco A.; Ribeiro, Sidarta; Malloy-Diniz, Leandro F. (Frontiers in Aging Neuroscience, 2014)
Semantic verbal fluency test is an important cognitive measure, broadly used in the neuropsychological assessment of the elderly, however its standards scores are less informative than what this task can provide. Graph theory represents a promising tool to understand a variety of neuropsychological states and this study presents a graph analysis of data generated by the semantic verbal fluency test in cognitive health elderly (NC), patients with Mild Cognitive Impairment – subtypes amnestic (aMCI) and amnestic multiple domain (a+mdMCI) - and Alzheimer’s disease (AD). The groups were compared when divided in three (NC – MCI – AD) and four groups. When the three groups were compared, significant differences were found in the standard measure of correct words produced, in the graph measures of diameter, the average shortest path, and on the density of the network. The graph measures also sorted the elderly in their groups with good specificity and sensitivity. When the four groups were compared the graph measures revealed significant difference between the groups in the density of the network, except between the two MCI subtypes and NC and aMCI. The diameter of the network and average shortest path were significant different between the NC and AD an aMCI and AD. Again the graph analysis sorted the elderly in their groups with good specificity and sensitivity, being better than the standard score of the task. These findings provide support for a new methodological frame to assess the strength of the semantic memory through the verbal fluency task, amplifying the predictive power of this test. The clinical use of graph analysis may likely give an important contribution to the differential diagnosis on elderly, helping in precocious diagnosis, and, consequently, improving prognosis.